Broadband Eight-Antenna Array Design for Sub-6 GHz 5G NR Bands Metal-Frame Smartphone Applications - Chen, Horng-Dean; Tsai, Yuan-Chung; Sim, Chow-Yen-Desmond; Kuo, Colin (IEEE antennas and wireless propagation letters, 2020)
A multiple-input-multiple-output (MIMO) antenna array for broadband 5G new radio (5G NR) metal-frame smartphone applications is proposed. The MIMO antenna array is realized by loading eight identical antennas (Ant1-Ant8) into the metal frame of the smartphone to form an eight-antenna array for the sub-6 GHz 8 × 8 MIMO system. Each antenna element is a slot antenna type that is composed of an L-shaped open slot and a 50 Ω microstrip feedline, and good impedance matching in the upper frequency band can be achieved by loading a tuning stub to the feedline. The 10 dB impedance bandwidth of the proposed eight-antenna array can cover the 5G NR Bands n77/n78/n79 and wireless local area network (WLAN) 5 GHz band. Besides demonstrating desirable antenna efficiency of 50%-82% and envelope correlation coefficient of <0.11, the isolations between adjacent array elements are also >12 dB. At 20 dB signal-to-noise ratio (SNR), the calculated peak channel capacity of the proposed eight-antenna array applied to an 8 × 8 MIMO system is 43.93 b/s/Hz.